Euro Adoption: Is It Reversible? - Cristina Puiu (CES Working Papers, 2010)
Starting from 1999 sixteen countries have adopted euro as a single currency. Considering that the Maastricht Treaty stipulates that all the European Union countries must adopt euro once they meet the requirements stipulated it is not a question of “if to join the euro area”, but rather of “when”. Therefore adopting euro currency is not and it should not be a reversible process. The decision to participate the monetary union represents the expression of a decision to move forward, while leaving it would be nothing else but a step back.
Keywords: 330; euro; reversibility; European Union; euro area; European Central Bank; Maastricht Treaty